PENGARUH KEPUASAN KERJA DAN KOMITMEN KERJA TERHADAP KINERJA GURU - Nova Hazna Afriani; Maswardi M Amin; Aswandi Aswandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to reveal the effect of job satisfaction and work commitment on the performance of PAUD teacher in Sintang district, both partially and jointly. The reseach method used is a quatitative approach with a type of causal comparative research or correlational study. This research was conducted in 12 PAUD institutions in Sintang District with the criteria of school intitutions in the form of KB and TPA education. While the sample was 54 PAUD teacher. The instruments used are in the form of questionnaires. Data collection procedures and techniques used were questionnaires. While the data analysis technique used inferential parametric statistics with the hypothesis testing technique is correlation analysis and multiple regression analysis with the help of  IBM SPSS Statistic 25 (SPSS 25). The conclusions of this research are as follows: (1) job satisfaction of Sintang District PAUD teacher tends to be low. (2) the work commitment  of Sintang District PAUD Teacher tend to be low. (3) T the performance of PAUD teachers in Sintang District tended to be low. (4) job satisfaction has a positive and significant effect on the performance PAUD teacher in Sintang District. (5) work commitment has a positive and significant effect of the performance of PAUD teacher in Sintang District. (6) job satisfaction has a positive and significant effect of the work commitment PAUD teacher in Sintang District, (7) job satisfaction and work commitment of teacher together have a positve and significant effect of the performance of PAUD teacher in Sintang DistrictKey Word : Job Satisfaction, Teacher Performance, Work Commitment